Type I IFN receptor blockade alleviates liver fibrosis through macrophage-derived STAT3 signaling - Soo-Jeung Park; Josefina Garcia Diaz; Josefina Garcia Diaz; Tina Comlekoglu; Young S. Hahn; Young S. Hahn (Frontiers in Immunology)
Liver macrophages play a role in the development of liver fibrosis progression via the regulation of inflammatory signaling. However, the precise mechanisms of macrophages contributing to liver fibrosis progression remain unclear. Using a preclinical model of CCl4-treated mice, we determined the composition of immune cells and the alteration of inflammatory gene expression. Our findings revealed a significant increase in liver macrophages, particularly those derived from infiltrating blood monocytes, in fibrotic mice. Moreover, the expression levels of type I IFN signature genes such as IFNα, IFNβ, ISG15, USP18, Ifi44, Ifit1, Ifit2, IRF3, and IRF7 were elevated in fibrotic mice. To determine the role of type I IFN signaling in liver fibrosis, we administered an IFNAR-1 antibody to block this pathway for 3 days prior to harvesting the liver. Notably, IFNAR-1 blockade reduced macrophage numbers compared to control mice and alleviated liver fibrosis in mice with increased hepatocyte proliferation and apoptosis. The ratio of P-STAT3/P-STAT1 in monocyte-derived macrophages was increased in the IFNAR-1 blockade group compared to fibrotic mice, and this was related to the appearance of M2 macrophage differentiation. Additionally, single-cell RNA-seq analysis indicated that IFNAR blockade affected inflammatory pathways involved in hepatocyte regeneration and fibrosis prevention. Taken together, IFNAR-1 blockade alleviates liver fibrosis progression by modulating macrophage inflammatory responses. These results provide insights for developing anti-fibrotic therapies against type I IFN signaling.